Research data sharing and valorization : developments, tendencies, models - Schöpfel, Joachim, 1957-; Rebouillat, Violaine (Sciences. Scientific knowledge management. Transformation dynamics of tools and practices, 2022)
As platforms for sharing, re-using and storing data, research data repositories are integral to open science policy. This book provides a comprehensive approach to these data repositories, their functionalities, uses, issues and prospects. Taking France as an example, the current landscape of data repositories is considered, including discussion of the idea of a national repository and a comparative study of several national systems. The international re3data directory is outlined and a collection of six case studies of model repositories, both public and private, are detailed (CDS, Data INRAE, SEANOE, Nakala, Figshare and Data Mendeley). Research Data Sharing and Valorization also includes appendices containing a number of websites and reference texts from the French Ministry of Higher Education, Research and Innovation, and the CNRS. To the authors' knowledge, it is the first book to be entirely devoted to these new platforms and is aimed at researchers, teachers, students and professionals working with scientific and technical data and information.